(untitled) (Ustozlar uchun, 2026)
This article examines the significant role of reading in improving English language skills. Based on research in Applied Linguistics, the study highlights how reading contributes to vocabulary acquisition, grammar development, cognitive growth, and overall language proficiency. The findings show that reading provides meaningful input, which is essential for effective language learning. The article also emphasizes the importance of extensive reading as a strategy to enhance fluency and comprehension. Scientific sources indicate that regular reading practice leads to long-term improvement in both receptive and productive language skills. Therefore, reading is considered a fundamental tool for mastering English.